Hydrogeological conditions ofsouthern Chiapas independencia township, Mexico - Reyes, Aurelio; Coras, Pablo; Arteaga, Ramón; Arana, Omar (Asuntos Económicos y Administrativos, 2013)
Independencia municipality in Estado de Chiapas,is located in the border region between Mexico and Guatemala. Itsphysiographyis characterizedby a succession ofplainsalternating withhills, forming part ofthe central high lands. The water resources are the Santo Domingo river, Porvenir river,Ibiltic river, Latonchic river, Matazan river and San Juan river. The climate is tropical subhumid with rains in summer, its annual medium temperatura is 21 ° C and its precipitation is 1.000mm per year. The Front of the Sierra de Chiapasis comprised of rocks from the Cretaceous to Recent, the largest elevations occur in limestone rocks in anticlinal folds, the synclinal ones are associated with plateaus; in one of them is located the Independencia municipality. The karst limestone rocks are associated with fracture (forming drains), these cracks are caused by tensional forces generating buried normal faults sequences. The limestone rocks are yellowish-gray at outdoor and whitish-gray in a fresh sample, they have sucrose texture, from fine to medium, with irregular fracture and many traces of dissolution. In the fractures observed on the surface, exist small caves or deep pools where the rainwater flows; the main problem with that, is the great amount of recent settlement on the zone, which brings pollution to the surface and subterranean waters, the deforestation, the water shortage and the wrong management of all types of waste. For this analysis, surface geology methods are used; the TERRAMETER SAS 300 in electric geophysics prospection and water chemical analysis for the hydrological characterization of the area. It is proposed to foment the reforestation, to increase the ecological conscience about the waste management, to reduce the drinkable water pollution, becausethere have been diseases like salmonella and cholera.